Presence of the pharmaceutical drug carbamazepine in coastal systems: effects on bivalves - Almeida, Ângela
Carbamazepine (CBZ), an antiepileptic drug, is one of the most commonly detected pharmaceutical drugs in aquatic ecosystems, and is used as a marker of urban pollution. Since CBZ is designed to exert a biological effect, when it reaches aquatic environment high probability exist for toxic effects on non-target organisms. The present study evaluated the acute toxicity of environmentally relevant concentrations of CBZ (0.00, 0.03, 0.30, 3.00, 9.00. ??g/L) in the edible clams Venerupis decussata (a native species) and Venerupis philippinarum (an invasive species) collected from the Ria de Aveiro. The effects on both species were assessed through the use of a battery of biomarkers mainly related with health status and oxidative stress. Furthermore, in this work an alternative and promising tool, the direct competitive immunoassay ELISA, for the direct CBZ quantification in clam's tissues, was applied. The results of the present work showed that CBZ in clam's tissues increased with the exposure concentration and V. decussata gave slightly higher values than V. philippinarum. Although the clams accumulated lower levels of CBZ than the concentration of exposure, these concentrations were enough to impair the health status and induce oxidative stress. However, a different response to CBZ was observed in the two species. While in V. philippinarum the lipid peroxidation levels increased at the highest CBZ concentration (9.00. ??g/L), in V. decussata a significant decrease was seen. Moreover, glutathionse S-transferase activity was stimulated in V. decussata and decreased in V. philippinarum. Nevertheless, an induction of glutathione reductase, superoxide dismutase and cytochrome P450 3A4 activities was found in both species as a result of the exposure. The results indicate that, probably, V. philippinarum have a less efficient antioxidant system than V. decussata, and are therefore less capable to neutralize oxidative stress and consequently more sensitive to CBZ. The risk quotient determined for the Ria de Aveiro was higher than 1 indicating that a ecotoxicological risk is suspected. Furthermore, bioaccumulation of CBZ in clams should be taken into consideration since this chemical might be transferred along the food chain and affect non-target organisms.